A pair of new lignan enantiomers from Croton tiglium. (December 2021) - Lu, Yan; Meng, Chun-Wang; Su, Hai-Guo; Xiong, Liang; Shu, Hong-Zhen; Liu, Jie; Lin, Qiao; Peng, Cheng; Cao, Xiao-Yu; Dai, Ou
Abstract: A pair of new 3′, 7-epoxy-8, 4′-oxyneolignan enantiomers [(+)-1 and (−)-1 ] as well as a known phenylpropanoid (2 ) were isolated from the seeds of Croton tiglium Linn. Their structures were established based on extensive spectroscopic analyses. The absolute configurations of (+)-1 and (−)-1 were determined by NMR data calculations and electronic circular dichroism calculations. All compounds were isolated from the genus Croton for the first time. Particularly, (+)-1 and (−)-1 were the first 3′, 7-epoxy-8, 4′-oxyneolignanes reported in Croton . The chemotaxonomic significance of these compounds was discussed. Graphical abstract: Image 1 Highlights: ● A pair of new lignan enantiomers and a known phenylpropanoid were isolated from Croton tiglium. ● All compounds were isolated from the genus Croton for the first time. ● This is the first time 3′, 7-epoxy-8, 4′-oxyneolignanes have been isolated from the genus Croton. ● This study revealed the chemotaxonomic significance of the isolated compounds in Croton.